Features of structural and geometric remodeling of the heart and changes in the diastolic filling of the heart in patients with chronic heart failure of ischemic genesis with preserved left ventricular ejection fraction - V. A. Lysenko; M. S. Potapenko; V. V. Syvolap (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
Chronic heart failure (CHF) is the most common cardiovascular disease worldwide, estimated at 23 million. With the increase in the growing of the elderly population, the prevalence of hypertension, atrial fibrillation, obesity, diabetes, as well as the improvement of ultrasound diagnostic methods, a further increase in the number of cases of CHF with preserved left ventricular EF.